Instructional Methods that Foster the Reading Development of Students with Significant Intellectual Disabilities - Wood-Fields, Colleen; Judge, Sharon; Watson, Silvana M.R. (Journal of Intellectual Disability - Diagnosis and Treatment, 2015)
Educational legislation has made reading a priority for students with significant intellectual disabilities (ID) and associated speech, language, sensory, or physical impairments. Historically, reading instruction for students with significant ID has focused on sight word instruction, with limited exposure to other essential reading skills. This article focuses on the evidence-based instructional methods that effectively and efficiently foster the reading development of students with significant ID. The authors reviewed the literature from the past 20 years on reading interventions for students with significant ID. In spite of access and opportunity barriers that have inhibited the reading development of students with significant ID, a synthesis of the empirical research on reading instruction suggests that students with significant ID and associated disabilities can learn phonemic awareness, phonics, vocabulary, fluency, and comprehension skills with direct instruction. Implications for providing reading instruction that effectively promotes reading development are discussed and areas for future research are identified.